Betalain- and betacyanin-rich supplements' impacts on the PBMC SIRT1 and LOX1 genes expression and Sirtuin-1 protein levels in coronary artery disease patients: A pilot crossover clinical trial. (September 2019) - Rahimi, Parisa; Mesbah-Namin, Seyed Alireza; Ostadrahimi, Alireza; Separham, Ahmad; Asghari Jafarabadi, Mohammad
Graphical abstract: Highlights: Betalain-/betacyanin-rich supplements increased levels of Sirtuin-1. Betalains-/betacyanins-rich supplements decreased the expression levels of LOX1. Betalain and betacyanin-rich extracts lowered plasma levels of hs-CRP in CAD patients. Abstract: Activation of Sirtuin-1 (SIRT1) is a considered candidate for the prevention of cardiovascular diseases. SIRT1 as a longevity factor regulates human cell lifespan and influences aspects of age-dependent atherosclerosis. Betalains can significantly increase the lifespan of  Caenorhabditis elegans . This effect may be agreeable with activation of SIRT1. Thus, this study investigates the effects of betalains on SIRT1 and Lectin-like Oxidized LDL Receptor 1 (LOX1) expression in coronary artery disease patients. Participants received three treatments (a betalains-rich supplement of red beetroot, a betacyanins-rich supplement of Opuntia stricta and a placebo; daily for two weeks) on three occasions which separated by washout periods. A notable elevation in SIRT1 levels and a considerable decrease in the expression levels of LOX1 and plasma concentration of high sensitive C Reactive Protein (hs-CRP) were observed after both supplementations. In conclusion, it appears that betalains could be considered as the new candidates in studies about age-related diseases.